A sensitive polymerase chain reaction based assay for the detection of Setaria digitata:The causative organism of cerebrospinal nematodiasis in goats,sheep and horses - Wijesundera, W.S.S.; Chandrasekharan, N.V.; Karunanayake, E.H. (Elsevier, 1998)
A sensitive PCR assay for the detection of Setaria digitata has been developed. Two oligonucleotide primers (17 nt) were designed from a previously cloned and characterized tandemly arranged repetitive sequence of Setaria digitata. Using these primers, it was possible to amplify small quantities (100 fg) of S. digitata genomic DNA. A simple procedure, using proteinase K and non-ionic detergent NP 40, was followed to process the host blood samples and mosquitoes harbouring L3 larvae. The sensitivity of the polymerase chain reaction based assay surpasses the microscopic detection and the previously reported oligonucleotide based chemiluminescent detection of microfilariae in infected host blood samples and L3 larvae in mosquitoes.
Keywords: Setaria digitata; Cerebrospinal nematodiasis; Diagnosis; Nematoda; PCR